2013
DOI: 10.1108/itp-12-2012-0147
|View full text |Cite
|
Sign up to set email alerts
|

Understanding computer security behavioral intention in the workplace

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 44 publications
4
53
0
Order By: Relevance
“…Consequently, in the online environment, it is expected that attitude facilitate transactions and reduce the barriers to the adoption of the terms of trade (Pavlou, 2002a,b), and more specifically, in our case, favour the intention to use mobile payment systems (Schierz, Schilke, & Wirtz, 2010). In line with previous research (Tsai, Zhu, Ho, & Wu, 2010;Yoon & Kim, 2013), we propose a similar relationship in the case of the new systems of payment. This results in the following hypothesis:…”
Section: Attitudesupporting
confidence: 77%
“…Consequently, in the online environment, it is expected that attitude facilitate transactions and reduce the barriers to the adoption of the terms of trade (Pavlou, 2002a,b), and more specifically, in our case, favour the intention to use mobile payment systems (Schierz, Schilke, & Wirtz, 2010). In line with previous research (Tsai, Zhu, Ho, & Wu, 2010;Yoon & Kim, 2013), we propose a similar relationship in the case of the new systems of payment. This results in the following hypothesis:…”
Section: Attitudesupporting
confidence: 77%
“…Many of these factors relate to the consequentialism ethical perspective, where factors such as perceived threat vulnerability (employees' perceptions of probability of harm occurring to organizations resulting from IS policy noncompliance behaviors) and perceived threat severity (employees' perceptions of severity of harm to organizations resulting from IS policy noncompliance behaviors if harm has occurred) [2,5,9,[19][20][21][22][23][24][25]. Concurrently, others have studied factors with the deontological focus, such as moral obligation (employees' perceptions of severity of harm to organization resulting from their noncompliance behaviors if harm has occurred) [23,[26][27][28][29][30]. However, regarding the virtue perspective, there was no evidence of any study examining factors relating to this perspective.…”
Section: Critical Review Of Is Literaturementioning
confidence: 99%
“…Compared with the results of Sommestad et al's systematic review [38], our findings were reassuring, with all of the journal articles identified by Sommestad et al that matched our inclusion and exclusion criteria included in our review. Furthermore, 15 additional journal articles were identified in our review but not included in Sommestad et al's review [2,3,20,23,24,26,27,[55][56][57][58][59][60][61][62].…”
Section: Search Processmentioning
confidence: 99%
See 2 more Smart Citations